Relationship Between the Bone Formation Rate and Functional Status in Symptomatic Knee Osteoarthritis - Demet TEKDÖŞ DEMİRCİOĞLU,; Nurdan PAKER,; Derya SOY BUĞDAYCI, (Archives of Rheumatology, 2011)
Objectives: This study aims to investigate the relationship between serum levels of bone-specific alkaline phosphatase and functional status in patients with symptomatic knee osteoarthritis (OA). Patients and methods: Seventy patients (57 females, 13 males; mean age 57.5±9.3 years; range 48 to 67 years) diagnosed with knee OA based on the American College of Rheumatology (ACR) criteria and 30 age- and gender-matched healthy controls (mean age 56.4±7.5 years) were enrolled in the study. Patients were evaluated using clinical, laboratory and radiographic methods. Bone-specific alkaline phosphatase and 24-hour urinary calcium and phosphorus levels were tested to assess bone metabolism. The Lequesne index was used for the severity of disease and the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) was used for the functional status. Results: The mean bone-specific alkaline phosphatase value was 13.69±4.76 mg/dl in the patient group. No statistically significant difference was found between the patient group and the control group in terms of bone-specific alkaline phosphatase values (p=0.584). The bone formation rate was high in 28.5% of the patients. A significantly positive correlation was found between the bone-specific alkaline phosphatase and the WOMAC stiffness scores (p=0.07, r=0.340). No significant correlation was found between the bone-specific alkaline phosphatase and the pain, physical function, and the total scores of the WOMAC and Lequesne index (p=0.590, r=0.090, p=0.489, r=0.107, p=0.413, r=0.139, p=0.285, r=0.70 respectively). Conclusion: In this study, an increase was shown in the bone formation rate in approximately 1/4 of the patients with symptomatic knee osteoarthritis. A significant positive correlation was found between bone formation rate and knee stiffness. However, no relationship was observed between the bone formation rate and pain, physical function, when they were compared with severity of the disease.